Blood Profile and Leukocyte Differentiation of Coturnix coturnix japonica with Addition of African Leaf Juice (V. amygdalina) in Drinking Water - Suci, Dwi Margi; Ratulangi, Cantika Rifki Yang; Hermana, Widya; Darmawan, Arif (Jurnal Sain Peternakan Indonesia, 2024)
This study aimed to assess the impact of incorporating African leaf juice into drinking water on the blood profile. A completely randomized design was used with 120 laying quail divided into three treatments and five replicates. The treatments included a control group (without African leaf juice) and two groups with African leaf juice added to their drinking water at 3 ml/bird/day doses and 6 ml/bird/day. The results showed that adding African leaf juice 3 ml and 6 ml/bird/day in drinking water decreased haemoglobin. Adding 3 and 6 ml/bird/day of African leaf juice in drinking water did not affect leukocyte differentiation. It was concluded that adding 3 ml/bird/day of African leaf juice could be used in quail drinking water.